Comparative study on bending and torsional effect of highly thermal graphene hybridization conductive ink - Ismail, Ismaniza (2023)
Electronic device printing on flexible and rigid substrates is advancing rapidly. Health, advertising, vehicles, transportation, energy, and electronics are among the sectors that employ this technology. Printing ink is an important component of printed electronics technology, with conductive inks being the most commonly used material. In recent years, researchers have investigated the combination of metal nanoparticles with graphene nanosheets. Hybrid conductive graphene inks for electronic applications have increased due to the addition of conductive polymers or metallic nanoparticles to improve graphene's original capabilities. Silver nanoparticle (AgNP) conductive ink dominates all metal-particle-based conductive inks for printed electronics. The objective of this study is to first formulate a new hybridization formulation between GNP and Ag. Besides, this new formulation of conductive ink has been investigated and characterised in terms of electrical and mechanical behaviour. The third was to evaluate the resistance and resistivity of the new conductive ink formulation using bending and torsion tests. Following that, research was carried out on the formulation and performance of GNP hybrids using GNP, silver flakes (Ag), and silver acetate (SA) as conductive fillers mixed with organic solvents to produce powder and paste. Then, the GNP hybrid paste was printed on a copper substrate using a mesh stencil method. The curing process involved in this experiment was 250°C per hour. The resistivity was evaluated at room temperature before the bending and torsional tests. After the test, the GNP hybrid formulation's reliability was evaluated in terms of electrical and mechanical resistivity. The resistivity value before performing the mechanical test was acceptable due to the lowest resistivity value in the range of 0.963 × 10-5 to 1.293 x 10-5 .m at room temperature. The finding exposed that the resistivity values for each of the three samples of bending and torsional tests significantly changed after 1000 cycles. However, the resistivity value of the torsional test at 5000 cycles was increased due to the damage impact of increasing the number of torsion cycles on the sample. Overall, the results revealed that this hybrid conductive ink has good resistivity and performs with acceptable reliability and durability. In future work, it is recommended that the conductive ink be printed on a more flexible substrate than copper, and the evaluation of temperature dependence can also be made more comprehensively.